Genetic suppression of polyglutamine toxicity in Drosophila. - Kazemi-Esfarjani, P.; Benzer, S. (Science, 2000)
A Drosophila model for Huntington's and other polyglutamine diseases was used to screen for genetic factors modifying the degeneration caused by expression of polyglutamine in the eye. Among 7000 P-element insertions, several suppressor strains were isolated, two of which led to the discovery of the suppressor genes described here. The predicted product of one, dHDJ1, is homologous to human heat shock protein 40/HDJ1. That of the second, dTPR2, is homologous to the human tetratricopeptide repeat protein 2. Each of these molecules contains a chaperone-related J domain. Their suppression of polyglutamine toxicity was verified in transgenic flies.